Occupational health of midwives - Richard Pougnet; Laurence Pougnet; Moriamo Eniafe-Eveillard; Brice Loddé (Nofer Institute of Occupational Medicine, 2020)
The midwifery profession varies greatly from one country to another. There are, however, a number of common features such as exposure to biological risks through contact with pregnant women and women in labor, exposure to postural stresses during examinations and medical acts, but also, increasingly, exposure to organizational constraints (work schedules, shift work, etc.). This article aims to give an overview of what is known about the occupational health risks of midwives (MWs). A review of the literature on Medline, from January 1, 2006 to December 31, 2017, was carried out. Articles focused principally on burnout (BO) and post-traumatic stress disorder. Several BO questionnaires were used. For the Copenhagen Burnout Inventory , the prevalence of personal BO ranged 20-57%; the percentage of work-related BO fell between 15-57%; and the prevalence of client-related BO ranged 5-15%. For the Maslach Burnout Inventory , the prevalence of emotional exhaustion varied between 23-60.7%; the prevalence of depersonalization ranged 3.3-30.3%; and the pervasiveness of personal accomplishment varied between 5-30.3%. There was little data concerning musculoskeletal problems or accidental exposure to biological fluids. The literature review on occupational pathologies demonstrates high levels of BO. Several gaps exist on the evolution of the impact of their work on the health of MWs, like the effect of shift work, postural stresses, etc. This review will make it possible to better focus future research on the occupational health of this population. Med Pr. 2020;71(4):473-81